Comparision Of Intraocular pressure measurements of Non-contact, Goldmann applanation and Schiotz tonometers - Alagöz, Gürsoy; Serin, Didem; Elçioğlu, Mustafa; Doğan, Ümit (Fırat University, 2006)
Objectives: We measured intraocular pressure (IOP) with noncontact, Goldmann applanation and Schiotz tonometers and compared the results of these three methods statistically. Materials and Methods: We measured intraocular pressure of 674 eyes of 422 patients with Cannon TX-10 non-contact tonometer, Goldmann applanation tonometer and Schiotz tonometer. All measurement methods were performed by the same physician. The data was statistically analyzed at 95% confidence interval; paired sample t-tests were performed for comparison of the methods. Results: In the entire group, the mean IOP values obtained by noncontact, Goldmann applanation and Schiotz tonometers were 18,50 ± 5,49 mmHg, 17,33 ± 5,48 mm Hg and 17,37 ± 5,30 mmHg, respectively. Conclusion: It can be concluded that if IOP value measured by noncontact tonometers is higher than the acceptable limits, it should be confirmed by other measurement methods. ©2006, Fırat Üniversitesi, Tıp Fakültesi

Amaç: Non-kontakt tonometre (NKT), Goldmann aplanasyon tonometresi (GAT) ve Schiotz tonometresi (SCH) ile yapılan göz içi basıncı (GİB) ölçümlerini karşılaştırmak. Gereç ve Yöntem: Polikliniğimize çeşitli şikayetlerle başvuran 422 hastanın 674 gözü çalışma kapsamına alındı. GİB'ları NKT, GAT ve SCH ile ölçüldü. Sonuçlar istatistiksel olarak karşılaştırıldı. Bulgular: NKT, GAT ve SCH ile ölçülen ortalama GİB değerleri sırasıyla; 18,50 ± 5,49 mmHg, 17,33 ± 5,48 mmHg ve 17,37 ± 5,30 mmHg olarak tespit edildi. NKT ile elde edilen ortalama GİB değerleri GAT ve SCH ölçümlerinden anlamlı derecede yüksek bulundu (p0.05). Sonuç: NKT ile yüksek ölçülen değerlerin diğer yöntemlerle teyit edilmesi gerektiği, düşük değerlerin ise başka bir bulgu söz konusu değilse güvenilir kabul edilebileceği görüşüne varıldı. ©2006, Fırat Üniversitesi, Tıp Fakültesi
Non-Kontakt, Goldmann Aplanasyon ve Schiotz Tonometre Ölçümlerinin Karşılaştırılması